Ascending aortas from heart donors and CABG patients are not equivalent as control in aortopathy studies. (3rd September 2018) - Forte, Amalia; Bancone, Ciro; Cipollaro, Marilena; De Feo, Marisa; Della Corte, Alessandro
Abstract: Objectives. A careful selection of reference samples in studies on the pathogenesis of thoracic ascending aorta (TAA) dilation is crucial for reliability, consistency and reproducibility of experimental results. Several studies include control TAA samples from heart donors. Others include samples harvested during coronary artery bypass graft (CABG) procedures or a mix of samples from heart donors and CABG patients. We verified the equivalence/homogeneity of TAA samples from heart donors and CABG patients in terms of basal gene expression and thus their reliability as reference groups in aortopathy studies . Design. We analysed by RT-PCR and Western blot the differential expression of smoothelin, α-smooth muscle actin (α-SMA) and transforming growth factor-β1 (TGF-β1), selected as major players in smooth muscle cell and myofibroblast phenotype and remodelling. The mean age and comorbidities of subjects were consistent with data routinely seen in clinical practice. Results. Data revealed the loss of smoothelin in samples from CABG patients, together with a significant increase of α-SMA, while TGF-β1 dimer showed a marked increase in CABG patients versus heart donors, accompanied by a decrease of the corresponding mRNA. Differences in gene expression were maintained after adjustment for age. However, TGF-β1 mRNA and CABG patients' age showed a positive correlation ( ρ = 0.89, p < .05), while α-SMA mRNA and age showed a negative correlation ( ρ = −0.85, p < .05). Conclusions. We revealed the non-equivalence of samples from heart donors and CABG patients, presumably for the presence of microscopic atherosclerotic lesions in CABG patients, suggesting the necessity of a careful selection of control groups in aortopathy studies.